PENDEKATAN DAKWAH DALAM MEMBINA PENGAMALAN AGAMA INA-INA - Nurwahida Alimuddin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
This paper deals with the religious practice of “ina-ina” female peddlers in Inpres Market Palu, and the analysis of pattern of da’wah (islamic preaching) which is relevant to them in order that they have comprehensive religious knowledge and implement it in their daily life. Islam is a religion that has values which lead human beings into a happiness in this world and the hereafter. However, if Islam is not disseminated, Islam will not give good impact on its adherents. It is why preaching becomes significant. Da’wah is intended to cultivate spiritual and mental of Muslims. If Muslims are spiritually and mentally good, they become part of agent who bring peace in this world.